Sanitary Surveillance Actions in clinical laboratories as to Compliance with Resolution no 302/2015 of the Collegiate Board of Directors of the Brazilian National Health Surveillance Agency - Goncalves Machado, Deusa Helena; Martins Machado, Jose Lucio [UNESP]; Achar, Eduardo; Dias, Cristiane Bitencourt (Fundacao Oswaldo Cruz, Escola Politecnica Saude Joaquim Venancio, 2016)
Introduction: This study focused on the effectiveness of municipal Sanitary Surveillance actions carried out in the context of clinical laboratories under the jurisdiction of the Regional Health Superintendence of Patos de Minas, state of Minas Gerais, Brazil. Objective: To verify if the Sanitary Surveillance followed eleven regulations set forth by Resolution No. 302/2015 of the Collegiate Board of Directors of the Brazilian Health Surveillance Agency when issuing sanitary permits to such laboratories. Methods: Data were collected from 181 annual health inspection reports from 2006 to 2013. Simple frequency and cross-checking analyses were carried out to treat data. Results: Sanitary Surveillance actions were still incipient in years 2006 and 2007. From 2008 on, however, there has been a significant increase in such actions, although they have shown to be less effective when it comes to compliance with items that are closely related to accuracy of laboratory tests and to the safety of patients and staff. Conclusion: the lack of effectiveness concerning Sanitary Surveillance actions is serious and brings out problems experienced by its team. Such problems ought to be investigated and resolved in order to improve the quality of the services provided by clinical laboratories.
Keywords: Health Surveillance; Clinical Laboratory; Health Legislation